Astana experience: department of oncohematology and bone marrow transplantation, National Research Center of Oncology and Transplantation - Kemaikin, Vadim M.; Olifirovich, Anastasiya A.; Kolesnev, Alexandr V.; Nemerovchenko, Anatoliy V.; Vildanova, Ruzal F.; Gainutdinova, Olga V.; Tusipova, Adiya A.; Esimbekova, Ayauzhan E.; Baimursina, Aliya K.; Suleimenova, Ayzat S.; Lesechko, Olga O.; Ansatbaeva, Gulnaz D.; et al. (Cellular Therapy and Transplantation (CTT)., 2017)
The Unit of Oncohematology and Bone Marrow Transplantation (BMT) was arranged on basis of the Republican Research Center of Hospital Emergencies SC (Astana, Republic of Kazakhstan) in August 2010. Since July 2014, a Clinical Department with 69 beds was arranged, and National Research Center for Oncology and Transplantation SC was arranged. From 2010 to 2016, the modalities of hematopoietic stem cell transplantation have been advanced, from autologous BMT to allogeneic hematopoietic stem cell transplants (HSCT) from matched donors (33%), and haploidentical HSCTs (43% in 2016), a total of 186 transpants. Bone marrow was used as a source of stem cells in 71 cases (71 donors for allo-HSCT in 69 recipients), whereas peripheral stem cells were harvested in 73 cases (15 donors for 15 recipients of allo-BMT, and 58 marrow harvests for autologous BMT).
Keywords: Hematopoietic stem cell transplantation, clinical advancements, Astana, Republic of Kazakhstan.